Protein Profiling of Selected Medicinal Plants of Central Karakoram National Park (CKNP), Gilgit-Baltistan, Pakistan: Protein Profiling of Selected Medicinal Plants - Abbas, Qamar; Khan, Sher Wali; Ismail, Muhmmad; Khaliq, Benish; Hussain, Azhar; Saif-Ud-Din; Raza, Ghulam; Alam, Ashia; Buck, Friedrich; Betzel, Christian (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
Medicinal plants are the treasure of nature for human beings. Mountain communities inhabited buffer zones of Central karakoram National Park (CKNP) are quite habitual in exploiting natural resources, especially for medicinal purposes. Three main potential medicinal plants from this area were selected based on their traditional applications and investigated further by protein profiling. Aerial parts of the selected plants namely; Delphinium brunonianum Royle, Gentiana tianschanica Ruprecht, Mém. and Saussurea simpsoniana (Fielding & Gardner) were used in our research study. Following the application of Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) technique, different protein bands were isolated and examined based on their diverse molecular weight (kD). Most of these proteins displayed low molecular weight ranged between 16 kD to 72 kD; while a few protein bands recorded higher molecular weight (72 kD). Total 16 types of protein bands were briefly examined through Liquid Chromatography-Mass Spectrometry LC-MS Analysis. This score showed the degree of significance of the identified proteins, while the taxonomy of viridiplantae score of > 44 indicated statistically significant match/ extensive homology at a confidence of p < 0.05. In this study, Rubisco was identified as a major protein while other protein types were identified (via LC/MS/MS) were very effective for diverse metabolic activities. To sum up, further research is required for the identified proteins in comparison with the data aerial parts and utilize it for advanced research, using X-ray crystallographic technique for the synthesis of these essential proteins.